A Contemporary Study of Musical Arts Informed by African Indigenous Knowledge Systems Volume 3 - Nzewi, Meki (African Minds, 2026)
There is as yet no comprehensive, learner-centred book that fosters African indigenous knowledge perspectives and rationalisation about the musical arts. The concern over the years has been for the production of research-informed books for modern, systematic education in African musical arts that derive in essence from the original African intellectual perspectives about the sense and meaning of music – indigenous to contemporary. The five volumes of the musical arts study series derive from 36 years of research and analytical studies in African musical arts. The volumes address the pressing need for learning texts informed by the indigenous African musical arts systems that target tertiary education. The texts incorporate knowledge of conventional European classical music as they relate to the unique features of African musical arts thinking and theoretical content. The contemporary African musical arts specialist needs secure grounding in his/her own human-cultural knowledge authority in order to contribute with original intellectual integrity to African as well as global scholarship discourse and knowledge creation.